Back Cover: Multi‐frequency (S, X, Q and W‐band) EPR and ENDOR Study of Vanadium(IV) Incorporation in the Aluminium Metal–Organic Framework MIL‐53 (ChemPhysChem 14/2015). Issue 14 (11th September 2015) - Nevjestić, Irena; Depauw, Hannes; Leus, Karen; Kalendra, Vidmantas; Caretti, Ignacio; Jeschke, Gunnar; Van Doorslaer, Sabine; Callens, Freddy; Van Der Voort, Pascal; Vrielinck, Henk
<x xml:space="preserve">Abstract</x> A successful method for doping the metal–organic framework Al‐MIL‐53 with vanadium ions is reported. By using multi‐frequency electron paramagnetic resonance and Q‐band electron–nuclear double resonance spectroscopy, it was demonstrated that VO units replace AlOH in the as‐synthesized metal‐organic framework structure. More details can be found in the Articles by H. Vrielinck et al. on page 2968 in Issue 14, 2015. (DOI: 10.1002/cphc.201500522).